Potentially inappropriate prescribing in elderly patients with epilepsy at two referral hospitals in Ethiopia - Tadesse, Tamrat Assefa; Belayneh, Alemu; Aynalem, Minychel Wale; Yifru, Yared Mamushet; Amare, Firehiwot; Beyene, Dessale Abate (Frontiers in Medicine, 2024)
Introduction The prevalence of drug therapy problems in patients with epilepsy has been reported to be as high as 70–90%. Moreover, elderly patients with epilepsy are highly vulnerable to inappropriate therapies. This study aimed to evaluate potentially inappropriate prescriptions (PIP) in elderly patients with epilepsy at the adult neurology clinics of two referral hospitals in Addis Ababa, Ethiopia. Methods A cross-sectional study was conducted on 81 patients with epilepsy and the medication appropriateness index (MAI), the Beers, and Screening Tool of Older Persons’ Prescriptions and Screening Tool to Alert to the Right Treatment (STOPP/START) criteria were used to assess PIP. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. Results Of the 81 study participants, 41(50.6%) were male, and the mean age was 67.33 ± 17.43 years. One-fourth of the study participants (25.9%) had polypharmacy and drug-drug interactions (DDIs) were documented in 64 (79%) patients. Based on the MAI, of the 263 medications that were prescribed for elderly epileptic patients, 110 (41.8%) had drug interactions, 44 (16.7%) had inappropriate indications, 31 (11.8%) were ineffective, and 12 (4.6%) were prescribed incorrect doses. Based on the STOPP and START criteria, PIP was reported in 31(38.3%) and 13(16.1%) patients, respectively. Conclusion Polypharmacy and DDIs are common in elderly epilepsy patients. The MAI, Beer’s criteria, and STOPP/START criteria indicate a high prevalence of PIP in elderly patients with epilepsy.